1996
DOI: 10.1172/jci118747
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in pressure overload-induced heart hypertrophy in the rat.

Abstract: Pressure overload induces cardiac growth in the rat, which implies the hypertrophy of cardiac muscle cells and proliferation of nonmuscle cells. The cardiac cell loss observed in parallel has generally been attributed to necrosis. Using an in situ assay, we demonstrated a phase of apoptosis or programmed cell death during the first 7 d after pressure overload with a peak at day 4 while cardiac growth continued for over 30 d. The increase in apoptosis was confirmed by quantification of 180-1500-bp DNA oligonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
169
2
9

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(187 citation statements)
references
References 25 publications
7
169
2
9
Order By: Relevance
“…Thus, the rate of apoptosis in normal human heart is B1 per 10 000 cardiomyocytes, but apoptosis increases several hundred-fold in ischemic and dilated cardiomyopathy and reactive cardiac hypertrophy (Narula et al, 1996;Teiger et al, 1996;Olivetti et al, 1997). Because adult cardiac myocytes are incapable of meaningful cellular regeneration (Rubart and Field, 2006), chronic persistent apoptosis at a rate of 0.1-1% of total cardiomyocytes, as is observed in human cardiomyopathies, may be sufficient to produce cardiac dilation and heart failure (Hayakawa et al, 2003).…”
Section: Cardiomyocyte Apoptosis and Bcl2 Proteins In Myocardial Diseasementioning
confidence: 99%
“…Thus, the rate of apoptosis in normal human heart is B1 per 10 000 cardiomyocytes, but apoptosis increases several hundred-fold in ischemic and dilated cardiomyopathy and reactive cardiac hypertrophy (Narula et al, 1996;Teiger et al, 1996;Olivetti et al, 1997). Because adult cardiac myocytes are incapable of meaningful cellular regeneration (Rubart and Field, 2006), chronic persistent apoptosis at a rate of 0.1-1% of total cardiomyocytes, as is observed in human cardiomyopathies, may be sufficient to produce cardiac dilation and heart failure (Hayakawa et al, 2003).…”
Section: Cardiomyocyte Apoptosis and Bcl2 Proteins In Myocardial Diseasementioning
confidence: 99%
“…Apoptosis occurs in the myocardium of patients with end-stage heart failure and myocardial infarction (MI), and in animal models of myocardial hypertrophy and failure [1][2][3]. Stimulation of β-adrenergic receptor (β-AR) induces apoptosis in cardiac myocytes in vitro and in vivo [4].…”
Section: Introductionmentioning
confidence: 99%
“…36 Noticeably, this cytoprotective effect may be weakened in hypertrophic heart because miR-133 levels have been found to be significantly reduced under such conditions and this may contribute to the increased tendency for the induction of apoptosis in hypertrophic myocytes. [37][38][39] Our study demonstrated that miR-1, another muscle-specific miRNA, promotes apoptosis induced by oxidative stress in cardiac cells and counteracts the effects of miR-133. 36 Intriguingly, an earlier study revealed that miR-1 levels are elevated by two-to threefold in ischaemic myocardium.…”
Section: How Many Mirnas Can Affect Apoptosis?mentioning
confidence: 64%